The Correlation between Critical Thinking Skills and Argumentation Skills of Biology Students: A Study across RQA, ADI, WE-ARe, and Conventional Learning - Astuti Muh. Amin (Postgraduate, University of Mataram, 2025)
The research explores the correlation between critical thinking skills and argumentation skills are still rarely found, especially in Biology lectures. Building an argument is actually a representation of students’ critical thinking skills and cognitive structure. This study investigates the correlation between critical thinking skills and argumentation skills among biology students exposed to RQA, ADI, WE-ARe, and conventional teaching strategies. The samples of this research were Biology education students in the fourth semester undergoing Animal Physiology. The data were analyzed by using regression analysis. Using regression analysis, significant correlation was only found in the ADI group (R² = 0.192, p < 0.05). These findings underscore the importance of using inquiry-driven models to enhance students' reasoning abilities. The results of this research are most likely affected by the students’ academic ability